KUALITAS MEDIA PEMBELAJARAN, MINAT BELAJAR, DAN HASIL BELAJAR SISWA: STUDI PADA MATA PELAJARAN EKONOMI DI KELAS X IIS SMA NEGERI 12 JAKARTA - Siti Saptari Qomariah; I Ketut R Sudiarditha (Faculty of Economics, State University of Jakarta., 2016)
This study aims to determine how much influence the quality of learning media and interest in learning towards the learning outcomes at senior high school level. The method used was a survey with the correlational approach. This study used path analysis techniques (Path Analysis). The results showed that the magnitude of the quality of learning media (X1) which directly affected the outcome of learning was 0.4092 = 0.167 or 16.7%, the influence of learning interest (X2) which directly affected the outcome of learning was 0.3552 = 0.126 or 12.6%, and the influence of the quality of learning media (X1) on learning outcomes (Y) moderated by the interest in learning (X2) was 0.154 or 15.4%. The influence of media quality and interest in learning altogether towards student learning outcomes can be seen from the coefficient of determination (R2), at 0.421, showing that the variation in student learning outcomes can be explained by the quality of learning media and learning interest, at 42.1%, while the other 57.9% was determined by other factors which were not examined. Simultaneously, the strength of the relation between the variable of learning media quality, learning interest and learning outcomes was strong, amounting for 0.649.